Pedagogies of Resilience amidst a Planetary Crisis: From Mind Training to Social and Environmental Justice - Rubén Flores; Ingrid Holme; Liam Fogarty (Teaching & Learning Inquiry: The ISSOTL Journal)
This article offers a circular framework for teaching and learning about resilience in higher education contexts. In order to navigate considerations of resilience as both potentially problematic and helpful, our framework stresses the importance of distinguishing between two different sets of questions: a) questions about the possibilities that humans have for cultivating qualities and skills that promote their flourishing, such as attention and mental balance, and b) questions about system change and social design from a social and ecological justice perspective. These questions are deeply implicated with one another, so one of the aims of our framework is to encourage students to explore the unity and mutual interdependencies between the two sets, as well as the possibilities of creating virtuous circles where the quest for nature restoration, social justice, and mental health sustain each other. In combining elements of “learning how” and “learning about,” this framework aspires to provide students with tools to make up their own minds about resilience, a term that has become all too present in public discourse and yet remains contentious. Alongside this framework, we also offer a summary of our pedagogical approach, one that stresses reflection, situated learning, and the use of the university campus as a playground to test ideas and build communities of learning.